Current-induced skyrmion motion on magnetic nanotubes. (25th March 2019) - Wang, Xiaofan; Wang, X S; Wang, C; Yang, Huanhuan; Cao, Yunshan; Yan, Peng
Abstract: Magnetic skyrmions are believed to be the promising candidate of information carriers in spintronics. However, the skyrmion Hall effect, due to the nontrivial topology of skyrmions, can induce a skyrmion accumulation or even annihilation at the edge of the devices, which hinders the real-world applications of skyrmions. In this work, we theoretically investigate the current-driven skyrmion motion on magnetic nanotubes which can be regarded as 'edgeless' in the tangential direction. By performing micromagnetic simulations, we find that the skyrmion motion exhibits a helical trajectory on the nanotube, with its axial propagation velocity proportional to the current density. Interestingly, the skyrmion's angular speed increases with the increase of the thickness of the nanotube. A simple explanation is presented. Since the tube is edgeless for the tangential skyrmion motion, a stable skyrmion propagation can survive in the presence of a very large current density without any annihilation or accumulation. Our results provide a new route to overcome the edge effect in planar geometries.